Implementation of Cooperative Learning Methods in Improving Reading Comprehension - Elin Herlina (International Journal Labs, 2022)
Background: Taggart consists of one cycle of one action, which begins with planning, action, observation, and reflection. This research was conducted in the odd semester of the 2017/2018 academic year, namely in October 2017. The subjects of this research were students of class X Catering Services (JB) SMK Negeri 1 Ciamis, totaling 31 people. The object of research is students' reading comprehension. Objectives: The purpose of this study was to determine the implementation of the Cooperative Learning Method in teaching reading comprehension, especially reading Factual Report texts to Class X Catering (JB) students at SMK Negeri 1 Ciamis, Ciamis District, Ciamis Regency, 2017/2018 Academic Year. Methods: This study uses qualitative data analysis and quantitative data analysis. Quantitative methods were used to analyze the data on students' reading test results (pre-test and post-test) which could be used to analyze statistical data on descriptive text learning materials. While the qualitative method was used to analyze data from observations, student questionnaires, and interviews. The data obtained from quantitative and qualitative methods are then compared and matched to obtain the conclusions from the research. Results: This type of research is Classroom Action Research (CAR) and the design of this research refers to Kemmis and Mc. Taggart's model consists of one cycle of one action, which begins with planning, action, observation, and reflection. This research was conducted in the odd semester of the 2017/2018 school year, namely in October 2017. Conclusion: The results showed that the Cooperative Learning Method could improve students' reading skills, especially in factual report texts.